Strategi Politik Lokal : Kemenangan Kandidat Muda dalam Pemilihan Legislatif oleh Partai Nasdem - Wahyu, Muhammad Wahyu Prasetyo Adi; Maksum, Ali (Universitas Medan Area, 2025)
Muhammad Farhan AlKatiri's victory in the Batu City legislative election is a form of regeneration of young leaders. Starting from his identity as a member of Generation Z, the individual's ability to disprove the stereotype of young people not being able to enter politics is shown. This research aims to dissect the strategy used by Farhan Alkatiri with the NasdemParty as the supporting party. This research uses a descriptive method with a qualitative approach that focuses on the strategy carried out by Farhan in the legislative election event. Data in this study were collected through interviews and social media documentation. Primary data sources are interviews with Farhan, Nasdem Party members, and Nasdem youth garda. At the same time, secondary data sources are recapitulation results and some relevant social media documentation. The results showed that Farhan's role as Generation Z in local politics is very innovative, that the strategy in absorbing electoral combined with the times without leaving conventional values. Among the strategies implemented are personal branding mass media with the composition of sharing content through the use of TikTok and Instagram platforms, the second strategy raises polemical issues related to waste management by assisting with waste processing equipment, the third strategy embracing young voters by maximizing the role of social media and conducting events with residents on the occasion of breaking the fast together in the fasting month. The four strategies were carried out massively by Farhan and the Nasdem Party so that the first victory by Generation Z in the political contestation of the Batu City regional legislature could be achieved.